Low-risk episode characteristics with an impact on total cost of care and performance in the Oncology Care Model. Issue 28 (1st October 2022) - Indurlal, Puneeth; Garey, Jody S.; Hoverman, John Russell; Mills, Lydia; Payne-De Bock, Judi; Staggs, Stuart; Wilfong, Lalan S.
Abstract : 12 Background: The Oncology Care Model (OCM) is an episode-based, Medicare value-based care program, that rewards providers for decreasing the total cost of care (TCOC) compared to a benchmark price. The model differentiates breast & prostate cancer treated with hormone-only therapy, and bladder cancer treated with Bacillus Calmette-Guérin and/or mitomycin as low-risk episodes (LRE). All other qualifying cancers, including breast, prostate & bladder cancer treated with chemotherapy are designated as high-risk episodes (HRE). Independent evaluation of OCM Performance Periods (PP) 1-6 suggests that reductions in TCOC predominantly occurred in HRE but were offset by increased TCOC in LRE. We seek to evaluate the episode characteristics that have a bearing on LRE performance in OCM. Methods: Episode claims data for 14 practices in The US Oncology Network (The Network) participating in OCM during PP 1-6 were assessed. Several episode characteristics including patient age, gender, comorbidities, cancer type, oncology touchpoints, etc. were evaluated. Results: LRE accounted for 30.5% of total episodes for The Network in OCM from PP1-6, with average benchmark price of 6, 700. 85% of LRE were breast cancer patients with average benchmark of 5, 800. Only 30% of LRE had increased TCOC exceeding benchmark. Average TCOC increased gradually with increasing age, with highest TCOC at extremes of patient age (18-64 and 80+). Episodes with multiple comorbidities (defined as Hierarchical Condition Category (HCC) flags 3, 4-5, 6+) had an average TCOC 3-times higher than episodes with fewer-or-no comorbidities (HCC flags 0, 1, 2). Episode expenses beyond cancer care (inpatient, nursing facility, home health, long term care, durable medical equipment, and inpatient rehabilitation) were 2.5 times higher for patients with advancing age (75-79 or 80+) and multiple comorbidities. Additionally, these patients had lower physician services expenses, fewer oncology care touchpoints (defined as visits with the Oncology practice), and a four-fold higher death rate. Conclusions: In the OCM, LRE for older patients with multiple comorbidities had higher TCOC, with fewer oncology touchpoints, higher death rates, and episode expenses beyond cancer care contributing the most to TCOC. Incorporating a comprehensive geriatric assessment (composed of physical, functional, cognitive, mental, and socioenvironmental factors) could guide oncologic therapeutic choices, and appropriate clinical management of these patients to improve outcomes. In addition, a modified, resource utilization-based risk adjustment approach could better fit this population.